Measurements of the Electrical Conductivity of Monolayer Graphene Flakes Using Conductive Atomic Force Microscopy - Soomook Lim; Hyunsoo Park; Go Yamamoto; Changgu Lee; Ji Won Suk (Nanomaterials, 2021)
The intrinsic electrical conductivity of graphene is one of the key factors affecting the electrical conductance of its assemblies, such as papers, films, powders, and composites. Here, the local electrical conductivity of the individual graphene flakes was investigated using conductive atomic force microscopy (C-AFM). An isolated graphene flake connected to a pre-fabricated electrode was scanned using an electrically biased tip, which generated a current map over the flake area. The current change as a function of the distance between the tip and the electrode was analyzed analytically to estimate the contact resistance as well as the local conductivity of the flake. This method was applied to characterize graphene materials obtained using two representative large-scale synthesis methods. Monolayer graphene flakes synthesized by chemical vapor deposition on copper exhibited an electrical conductivity of 1.46 ± 0.82 × 106 S/m. Reduced graphene oxide (rGO) flakes obtained by thermal annealing of graphene oxide at 300 and 600 °C exhibited electrical conductivities of 2.3 ± 1.0 and 14.6 ± 5.5 S/m, respectively, showing the effect of thermal reduction on the electrical conductivity of rGO flakes. This study demonstrates an alternative method to characterizing the intrinsic electrical conductivity of graphene-based materials, which affords a clear understanding of the local properties of individual graphene flakes.